2021
DOI: 10.1108/jmlc-10-2021-0116
|View full text |Cite
|
Sign up to set email alerts
|

Does holding offshore jurisdictions to higher AML standards really assist in preventing money laundering?

Abstract: Purpose This paper aims to contend that when tackling financial crimes such as money laundering and terrorist financing, international regulators are seeking to hold offshore jurisdictions such as the Cayman Islands to higher standards and that this detracts from the pursuit of detecting and prosecuting money launders. Design/methodology/approach This paper will deal with the following perceived issues: firstly, to offshore jurisdictions as a concept; secondly, to outline the efforts made by the Cayman Islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To address this perpetual challenge, continuous training programs for cybercrime investigators must be implemented (Sultan & Mohamed, 2022). These programs should focus on the latest cyber threats, advancements in digital forensics techniques, and emerging trends in cybersecurity (Perkins, 2021). Collaborative initiatives involving law enforcement agencies, academia, and the private sector can facilitate the timely exchange of knowledge and expertise, fostering a collective ability to stay ahead of malicious actors in the rapidly evolving cyber landscape (Tiwari et al, 2022).…”
Section: Difficulty In Keeping Pace With Evolving Cyber Techniquesmentioning
confidence: 99%
“…To address this perpetual challenge, continuous training programs for cybercrime investigators must be implemented (Sultan & Mohamed, 2022). These programs should focus on the latest cyber threats, advancements in digital forensics techniques, and emerging trends in cybersecurity (Perkins, 2021). Collaborative initiatives involving law enforcement agencies, academia, and the private sector can facilitate the timely exchange of knowledge and expertise, fostering a collective ability to stay ahead of malicious actors in the rapidly evolving cyber landscape (Tiwari et al, 2022).…”
Section: Difficulty In Keeping Pace With Evolving Cyber Techniquesmentioning
confidence: 99%
“…Tax evasion and regulatory evasion have also been identified as drivers of perceived jurisdiction risk. Cotoc et al (2021) found that tax evasion is positively associated with perceived money laundering risk in the EU, while Perkins (2022) found that regulatory evasion is a significant driver of perceived money laundering risk in the UK. Regulatory stringency has also been examined as a driver of perceived jurisdiction risk, with FCA (2021a, 2021b) finding that perceived regulatory stringency is positively associated with perceived money laundering risk in the UK.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As firms' perceptions of financial crime risk at a jurisdiction level rapidly gain supervisory relevance and international firms continue to reconsider their operations in high-risk jurisdictions, it is imperative to bring empirical evidence to bear on the question of whether political stability, evasion of tax and regulations and regulatory stringency explain firms' perceptions of jurisdiction risks (FCA, 2021a). While different measures of financial crime risk exist, it is notoriously challenging to capture firms' perceptions of it, particularly at a cross-jurisdiction level (Simser, 2013;Cotoc et al, 2021;Perkins, 2022). Financial crime risks can vary significantly across different jurisdictions due to differences in legal and Crossjurisdictional financial crime risks regulatory frameworks, cultural norms and levels of economic development.…”
Section: Introductionmentioning
confidence: 99%